Pola Asuh Makan Anak Stunting Usia 6 – 24 Bulan di Desa Serdang Kabupaten Bangka Selatan - Zenderi Wardani; Emilia Emilia; Ovi Andari (JGK:Jurnal Gizi dan Kesehatan, 2022)
Background: Inadequate parenting, especially in terms of behavior and feeding practices, is one of the factors of stunting. Purpose: This study aimed to describe and analyze the relationship between parenting and eating patterns in cases of stunting of under-5 years children in Serdang Village, Working Area of the Rias Health Center, South Bangka District. Method: This study used a quantitative method with a cross-sectional design conducted from May to June 2022. The study population was all toddlers aged 6-24 months, with a sample size of 32 under-5 years children selected using a simple random sampling technique. Data collection on parenting and eating patterns used a questionnaire, and the determination of nutritional status with the height/age index was carried out using the WHO Anthro software. Data analysis was carried out through descriptive analysis,and correlation analysis was performed using spearman rank test. Results: The results showed that the problem of stunting was still a public health problem (33.3%), with low parenting styles on the demandingness and responsiveness aspects of 54.5% and 72.7%, respectively. Conclusion: There is a relationship between the demandingness aspect of parenting and stunting (ρ=0.04). This study recommends nutrition education interventions related to infant and child feeding (IYCF) accompanied by increased family economic empowerment.